Open Personal Identity as a Service - Miroslav Behan (Journal of Computer Networks and Communications)
The mobile computing established communication environment where personal identification is a key factor which influence usability of mobile application. Open personal identity is a partial service which enables crowd resource identifications processing in online distributive unified form over secured communication channel. The service provides current fresh personal identificators which are essential in communication process.